Diagnostic accuracy and value of chromosomal microarray analysis for chromosomal abnormalities in prenatal detection: A prospective clinical study. Issue 20 (21st May 2021) - Huang, Hailong; Wang, Yan; Zhang, Min; Lin, Na; An, Gang; He, Deqin; Chen, Meihuan; Chen, Lingji; Xu, Liangpu
Abstract : Abstract: Chromosomal microarray analysis (CMA) has emerged as a primary diagnostic tool for the evaluation of developmental delay and structural malformations in children. The aim of this study was to compare the accuracy and value of CMA and karyotyping on diagnosis of chromosomal abnormalities in Fujian province of South China. In the study, 410 clinical samples were collected from pregnant women between March 2015 and December 2016, including 3 villus (0.73%, 3/410), 296 amniotic fluid (72.20%, 296/410), and 111 umbilical cord blood (27.07%, 111/410). All samples were screening for chromosomal abnormalities by both using CMA and karyotyping. The success rate of CMA and karyotyping was 100% (410/410) and 99.27% (407/410), respectively. Sixty-one (14.88%, 61/410) samples were presented with chromosomal abnormalities by using CMA, whereas 47 (11.55%, 47/407) samples were shown with chromosomal abnormalities by using karyotyping. Thirty-one (8.61%, 31/360) samples with normal karyotypes were found to exist chromosomal abnormalities by using CMA. Receiver operating characteristic analysis showed that the area under the curve of karyotyping on the diagnosis of chromosomal abnormalities was 0.90 (95% confidence interval: 0.87–0.93), the sensitivity and specificity was 87.56% and 91.22%, respectively. The area under the curve of CMA on the diagnosis of chromosomal abnormalities was 0.93 (95% confidence interval: 0.90–0.95), with 90.68% sensitivity and 94.40% specificity. Notably, the combination of CMA and karyotyping could improve the diagnosis of chromosomal abnormalities. CMA has a better diagnostic value for screening chromosomal abnormalities, especially for those pregnant women with normal karyotypes. This study has guiding value for prenatal diagnosis in Fujian province of South China. Abstract : Supplemental Digital Content is available in the text